흰쥐를 이용한 실험적 맥락막신생혈관 모델에서 유리체강내 양막 주입의 효과 - 이종현; Jong Hyun Lee; 정재림; Jae Lim Chung; 홍사민; Sa Min Hong; 고형준; Hyoung Jun Koh (Daihan angwa haghoi jabji, 2008)
목적: 흰쥐의 실험적 맥락막신생혈관 모델에서 유리체강내 양막 주입의 효과를 알아보고자 하였다. 대상과 방법: 레이저 조사 직후 15마리 흰쥐의 좌안에 양막(12.5 μg/mL)을, 우안에는 인산염완충식염수를 유리체강내 주입하였다. 레이저 조사 2주째에 형광안저혈관조영술 시행 후, 쥐를 희생하여 조직병리학 검사를 시행하였다. 맥락막신생혈관 성장에 관한 양막의 효과를 알아보기 위하여 두 그룹 사이의 안저혈관조영검사 및 조직병리검사 결과를 비교하였다. 결과: 맥락막신생혈관의 두께는 양막처치군(141.54±8.12 ?m)에서 대조군(65.23±16.90 μm)에 비해 통계적으로 유의하게 증가하였다(p=0.010). 결론: 유리체강내 양막의 주입은 흰쥐 맥락막신생혈관 모델에서 조직병리학적으로 혈관형성 촉진효과를 보여주었다. <한안지 49(7):1154-1158, 2008> Purpose: To evaluate the effects of an intravitreal amniotic membrane (AM) injection on a rat model of laser-induced choroidal neovascularization (CNV). Methods: Intravitreal injection of AM (12.5 μg/mL) into the left eyes and phosphate-buffered saline into the fellow eyes of 15 rats was performed immediately after laser injury. At week 2, after angiography, the rats were sacrificed, and histopathologic analysis was performed. Angiographic and histopathologic assessments of the effects of AM injection on CNV growth were compared between the two groups. Results: CNV thickness was found to have increased more in the AM treatment group (141.54±8.12 μm) than in the experimental control group (65.23±16.90 μm) (p=0.010). Conclusions: Intravitreal AM injection demonstrated histopathologic pro-angiogenic properties in a rat model of CNV. J Korean Ophthalmol Soc 49(7):1154-1158, 2008